Objective Assessment of Sunburn and Minimal Erythema Doses: Comparison of Noninvasive In Vivo Measuring Techniques after UVB Irradiation. (10th May 2010) - Huang Huang, Min-Wei Min-Wei; Lo Lo, Pei-Yu Pei-Yu; Cheng Cheng, Kuo-Sheng Kuo-Sheng
Abstract : Military personnel movement is exposed to solar radiation and sunburn is a major problem which can cause lost workdays and lead to disciplinary action. This study was designed to identify correlation parameters in evaluating in vivo doses and epidermis changes following sunburn inflammation. Several noninvasive bioengineering techniques have made objective evaluations possible. The volar forearms of healthy volunteers (n = 20 ), 2 areas, 20 mm in diameter, were irradiated with UVB 100 mj/cm 2 and 200 mj/cm 2, respectively. The skin changes were recorded by several monitored techniques before and 24 hours after UV exposures. Our results showed that chromameter a ∗ value provides more reliable information and can be adopted with mathematical model in predicting the minimal erythema dose (MED) which showed lower than visual assessment by 10 mj/cm 2 (Pearson correlation coefficient ℑ = 0.758 ). A more objective measure for evaluation of MED was established for photosensitive subjects' prediction and sunburn risks prevention.